Modelling of proportional integral voltage controller for distributed generation during islanding operation - Mohd Shari, Nurul Syuhada (2020)
A microgrid is defined as a part of an electric power distribution network that is formed by the interconnection of energy source and energy storage. Microgrid operates as a single controllable system that provides power to its local area that can be a residential, commercial or industrial. Main function of microgrid is to ensure the stable operation during normal, fault and variety of network disturbance. It can be disconnected from the rest of the power system either non-intentional or intentional. This leads to concerns over the efficiency, safety and stability of the voltage, frequency and power at microgrid. The operation and control of a microgrid is challenging especially in an off-grid scenario where microgrid is isolated from main utility grid. This situation is known as islanded mode of the operation. When an islanding occurs, the voltage and frequency are out of safety limit as the islanded area cannot be controlled by the grid. This thesis is focused on designing voltage control schemes in low voltage networks by using PSCAD software. The voltage control model then was developed by implementing the droop characteristics with Proportional Integral (PI) controller to control voltage. This thesis also focused on evaluating and analyzing the performance of voltage control schemes of the Distribution Generation (DG) when subjected to islanding and network disturbances. The results show that voltage control scheme can regulate and recover the voltage to its nominal limit during islanding events; normal, fault and network disturbance.